Peningkatan Usaha Produk Asal Hewan Sesuai Sni Halal Pada Industri Rumah Tangga di Desa Laban Kecamatan Menganti Kabupaten Gresik: Improvement of Animal Products Businesses in Accordance with SNI Halal in Home Industries in Laban Village, Menganti District, Gresik Regency - Miyayu Soneta Sofyan; Moh. Sukmanandi; Siti Eliana Rochmi (IGKOJEI: Jurnal Pengabdian Masyarakat, 2021)
ABSTRACT Merchants in Laban Village, Menganti District, Gresik Regency, which has a diverse population and different beliefs, require knowledge of the importance of SNI in the ‘halal’ field in the household industry. The lack of awareness about ASUH (safe, healthy, whole, and halal) food ingredients, food hygiene and halal certification causes people to ignore the important role of public health risks that may come from food. The business concept is still traditional. Food processing is still relatively simple, so it has not reached optimal results. The potential of merchants as a driving force for the people's economy in that particular village is quite large but it is still not supported with knowledge regarding proper ASUH meat and food hygiene. The goal of this community service is to raise the public awareness of emerging diseases from food, along with improving the health standard of animal-based products business under the SNI in the Halal sector in the Food Household Industry in Gresik Regency and thus improving the income of food entrepreneurs selling processed animal-based food. The method used in this community service is to guide animal health to street vendors selling processed materials derived from livestock followed by SNI training and the process of halal certification submission. The main idea of the focus group discussion is about how to obtain ASUH meat and its processing application. The evaluation of this activity is a pre and post-test for the community service participants. The result of this community service is an increase in the awareness of SNI in the halal sector in the home industry and an increase in regulations regarding the flow of obtaining halal certification for processing basic products from livestock along with the increase of knowledge and skills of community service participants. In conclusion, the community service activity has a positive impact on the implementation of halal SNI in household industries in Laban Wetan village to achieve halal certification. Keywords: SNI; Halal; Certification; Pelapak ABSTRAK Pelapak di Desa Laban Kecamatan Menganti Kabupaen Gresik dengan penduduk dan latar belakang keyakinan yang majemuk memerlukan pengetahuan pentingnya SNI bidang halal pada industry Rumah Tangga . Minimnya kesadaran tentang bahan pangan yang asuh, higyne pangan dan sertifikasi halal menjadikan masyarakat kurang memahami peran penting terhadap kesehatan masyarakatnya yang bisa disebabkan oleh makanan.Konsep usaha yang masih tradisional. Pengolahan pangan masih relative sederhanan sehingga belum mencapai hasil yang optimal. Potensi pelapak sebagai penggerak ekonomi rakyat di Desa tersebut cukup besar tetapi masih belum diimbanagi dengan pengetahuan tentang daging asuh , dan kesehatan makanan. Peningkatan public awarnes terhadap emerging disease penyakit akibat pangan Peningkatan kesehatan terhadap usaha produk asal hewan sesuai SNI bidang Halal pada Industri Rumah Tangga Pangan di kabupaten Gresik sehingga meningkatkan pendapatan pelaku usaha makan berbahan dasar olahan dari hewan. Metode yang digunakan dalam pengabdian kepada masyarakat ini adalah dengan pembinaan pada para pelapak pedagang kaki lima yang menjual bahan olahan yang berasal dari ternak,sni , kesehatan ternak,dilanjutkan dengan pelatihan alur SNI dan pengajuan sertifikasi halal. Pelksanaan focus group discussion mengenai cara mendapatkan daging asuh, dan aplikasi pengolahannya. Evaluasi kegiatan ini adalah pre dan post test peserta pengmas. Hasil dari pengmas ini adalah adanya peningkatan kesadaran SNI bidang halal pada industry rumah tangga dan peningkatan pengatuan tentang alur mendapatkan sertifikasi halal untuk olahan produk bernahan dasar dari hasil ternak. dan peningkatan pengetahuan serta ketrampilan peserta pengmas. Kegiatan Pengmas memberikan dampak yang positif terkait pelaksanaan SNI halal pada industry rumah tangga di desa laban wetan untuk mencapai sertifikasi halal. Kata kunci: SNI; Halal; Sertifikasi; Pelapak